1981
DOI: 10.1203/00006450-198112000-00143
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's syndrome secondary to ACTH-secreting Wilms'Tumor

Abstract: HLA and hormonal studies in families of patients with 21-hydroxylase deficiency -cryptic patients?The study comprises 14 families with unaffected siblings and with one or two children (total 17) with congenital adrenal hyperplasia (CAH)-21 OH defect. HLA tissue tY1inf and glyoxalase~GlOf confirmed the close genet~c~age between 21 0 de. and HLA-B locus. Positive association with B 47 was found: in 2 of 18 unrelated patients (normal population 0.4%, p < 0.01), negative association to B 8 (only one positive), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…11]. In a review of the literature, we only found one record of Wilms' tumor producing adrenocorticotropic 1 A preliminary report has been published [8].hormone [ACTH; I] although the 'ectopic ACTH syndrome' has not infrequently been seen with other tumors [9]. The following case of Cushing's syndrome due to an ACTH-secreting Wilms' tumor is, therefore, presented as the 2nd case.…”
mentioning
confidence: 99%
“…11]. In a review of the literature, we only found one record of Wilms' tumor producing adrenocorticotropic 1 A preliminary report has been published [8].hormone [ACTH; I] although the 'ectopic ACTH syndrome' has not infrequently been seen with other tumors [9]. The following case of Cushing's syndrome due to an ACTH-secreting Wilms' tumor is, therefore, presented as the 2nd case.…”
mentioning
confidence: 99%